2002
DOI: 10.1097/00007890-200204270-00020
|View full text |Cite
|
Sign up to set email alerts
|

Activation of human endothelial cells by mobilized porcine leukocytes in vitro

Abstract: Porcine PBPC activate HUVEC, as suggested by an increase in surface E-selectin, VCAM-1, and ICAM-1 levels, and have a maximum effect after 9 hr. Freezing of PBPC does not affect PBPC-induced activation of HUVEC. PBL induce greater activation of HUVEC than do PBPC. CD2- cells are primarily responsible for PBPC-induced activation of HUVEC and direct cell-cell contact is required. Removal of CD2- cells before the administration of PBPC or the use of agents that interrupt PBPC-endothelial cell interactions may pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Our results are in agreement with Fries et al (42) who reported the maximal transcript levels both for VCAM-1 and for E-selectin at 3 to 6 hours in various mouse tissues after lipopolysaccharide administration. They are in keeping with Appel et al (43) who demonstrated in a xenogeneic in vitro model that porcine peripheral blood lymphocytes induced high levels of E-selectin and VCAM-1 after direct cell-cell contact. TNF-␣ is known to induce ICAM-1, VCAM-1, and E-selectin expression in EC cultures (44 -47).…”
Section: Discussionsupporting
confidence: 90%
“…Our results are in agreement with Fries et al (42) who reported the maximal transcript levels both for VCAM-1 and for E-selectin at 3 to 6 hours in various mouse tissues after lipopolysaccharide administration. They are in keeping with Appel et al (43) who demonstrated in a xenogeneic in vitro model that porcine peripheral blood lymphocytes induced high levels of E-selectin and VCAM-1 after direct cell-cell contact. TNF-␣ is known to induce ICAM-1, VCAM-1, and E-selectin expression in EC cultures (44 -47).…”
Section: Discussionsupporting
confidence: 90%
“…Using the HUVEC assay with a transwell membrane permeable to cytokines but not to PBPC, Appel et al demonstrated that direct cell–cell contact is also required for the activation of HUVEC by PBPC [8]. Furthermore, Benatuil et al recently showed that peripheral blood mononuclear cells, but not activated HUVEC or culture supernatant of activated HUVEC, are able to generate thrombin when added to defibrinated human plasma [18].…”
Section: Discussionmentioning
confidence: 99%
“…The extent of PBPC‐induced activation of HUVEC is dependent on the duration of time for which these cells are permitted to interact [8]. VCAM‐1, ICAM‐1, and E‐selectin expression on HUVEC were increased as early as 3 h after the addition of Gal + PBPC, with maximum levels being reached after approximately 9 h. Expression then remained stable for at least 24 h. The incubation of HUVEC with PBPC or BM cells in the current experiments was discontinued after 14 to 16 h in order to assess the effect of maximal stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations